2017
DOI: 10.1063/1.4985308
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of excitation temperature by duty ratio of observed period in non-equilibrium plasma

Abstract: We investigated the excitation temperature of atmospheric-pressure non-equilibrium (cold) plasma using a line-pair method. An atmospheric cold plasma was intermittently generated using a quartz tube, a rare gas, and a foil electrode by applying high-voltage alternating current. Because the plasma occurred intermittently, an interval appeared between each generated plasma bullet. We assessed the time-averaged effective intensity from the observed intensity at each wavelength measured using a spectrometer. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The characteristic spectral lines of helium were chosen to determine the excitation temperature ( T exc ) under a Boltzmann approximation [ 28 , 29 ]. Fig 3(C) presents the excitation temperature of the jet array as a function of the pulse width.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic spectral lines of helium were chosen to determine the excitation temperature ( T exc ) under a Boltzmann approximation [ 28 , 29 ]. Fig 3(C) presents the excitation temperature of the jet array as a function of the pulse width.…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of APPJs is important for understanding thermodynamic properties including gas temperature (T g ), rotational temperature (T rot ), excitation temperature (T exc ) and electron temperature (T e ) in the plasma [16][17][18][19]. Optical emission spectroscopy (OES) is a widely used technique to investigate such properties using experimental observations [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The excitation temperature (T exc ) describes the population of atomic excited states assuming that this follows a Boltzmann distribution. Considering the degeneracy of each atomic state, the population come by [18,19,41], and the CR model was applied to estimate the relations between the thermodynamic properties of AP-PJs. The distribution of chemical species along the direction of plasma jet propagation was estimated numerically using the GM.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Plasma parameters (density and temperature) change with operation conditions, but with typical parameters, atmospheric-pressure nonequilibrium (cold) plasma can have a wide-ranging density of 10 17 -10 20 m -3 , and its temperature can be a few electron volts. 5,6,19,[24][25][26] Plasma intermittently generated by AC power supply is in a nonthermal equilibrium state. One study reported such plasma's electron temperature to be ~1 eV, 26 but ion and gas temperatures were close to room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,19,[24][25][26] Plasma intermittently generated by AC power supply is in a nonthermal equilibrium state. One study reported such plasma's electron temperature to be ~1 eV, 26 but ion and gas temperatures were close to room temperature. 11 Therefore, it is thought that thermal damage to an object does not occur with plasma irradiation.…”
Section: Introductionmentioning
confidence: 99%